Postdramatic Theatre, 12 years later - Hans-Thies Lehmann (Johann Wolfgang Goethe-Universität Frankfurt am Main – Frankfurt, Alemanha) (Revista Brasileira de Estudos da Presença, 2013)
This text takes stock of the twelve years of emergence of the practice and term Postdramatic and some of its developments and issues in the performing arts. It discusses the changes through which the contemporary scene has gone since 1999 and consequently the changes we should consider when reading and analysing the concept of postdramatic; among them, the focus on collaborative work; new relations between theatre and society; the focus on dance; and the return of words. Finally, the text raises the question of whether or not the term postdramatic should be reconsidered.